New Avenues for Anticoagulation in Atrial Fibrillation. Issue 1 (5th December 2012) - Mantha, S; Cabral, K; Ansell, J
<x xml:space="preserve">Abstract</x> Vitamin K antagonists (VKAs) were, until recently, the only option for chronic anticoagulation in patients with atrial fibrillation. Three new oral anticoagulants have been tested for this indication in recent randomized trials: dabigatran, rivaroxaban, and apixaban. They offer the promise of consistent effect without the need for monitoring drug levels. Overall, efficacy and safety appear to be noninferior, and in some instances superior, to warfarin. However, the new drugs have their downsides, and switching from warfarin is not recommended for all patients. This review focuses on the available evidence and attempts to provide guidance to clinicians in the field. Clinical Pharmacology & Therapeutics (2013); 93 1, 68–77. doi:10.1038/clpt.2012.197